The Modern Cult of Efficiency: Intermediary Organizations and the New Scientific Management. (March 2014) - Trujillo, Tina
This article analyzes one intermediary organization. It draws on critical policy studies to frame the agency's behaviors amid a discourse of managerialism in the public sector, and critical studies of education markets to explain the relationships between its reforms and education policy. Findings illustrate how the intermediary enacted managerial data monitoring systems as the core drivers of its reforms; how it framed leadership and teaching as reductive, managerialist pursuits; and why its reliance on business-inspired logics, roles, and language enabled it to compete in a marketplace and preserve its industry niche. In this way, its behaviors resembled those of the "efficiency experts" during the industrial revolution. The result was an intermediary that erroneously equated data with professional judgment, and that guided decisions based not on a century's worth of evidence about the limitations of purely managerial reforms, but on an enduring ideological faith in technocratic solutions to complex social problems.